2019
DOI: 10.1016/j.ssc.2019.113735
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of α-boron and some boron-rich pnictides

Abstract: Thermal expansion of α-rhombohedral boron (α-B12) and two isostructural boron-rich pnictides (B12P2 and B12As2) has been studied between 298 and 1280 K by high-temperature synchrotron X-ray diffraction. For all studied phases no temperature-induced phase transitions have been observed. The observed temperature dependencies of the lattice parameters and unit cell volumes were found to be quasi-linear. Variation of the thermal expansion coefficients in the group of boron-rich pnictides (B13N2 -B12P2 -B12As2) was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…It was found that with an increase in the Al 12 Mg 17 -B powder content in the initial powder mixture, the hardness of sintered materials increases. This is due to the formation of compounds based on B 12 icosahedrons (AlB 12 , B 4 Si, B 6 Si) with high hardness [ 3 , 4 , 5 ]. At a content of 70 wt% of Al 12 Mg 17 -B powder in the initial mixture, the hardness of the composite reaches 21.24 ± 1.22 GPa.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that with an increase in the Al 12 Mg 17 -B powder content in the initial powder mixture, the hardness of sintered materials increases. This is due to the formation of compounds based on B 12 icosahedrons (AlB 12 , B 4 Si, B 6 Si) with high hardness [ 3 , 4 , 5 ]. At a content of 70 wt% of Al 12 Mg 17 -B powder in the initial mixture, the hardness of the composite reaches 21.24 ± 1.22 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…Higher borides belong to the group of compounds based on B 12 icosahedrons. The main compounds based on B 12 icosahedrons are AlB 12 , B 12 C 3 (B 4 C), B 12 Si 3 , B 12 Si 2 (B 4 Si and B 6 Si), and B 12 O 2 (B 6 O) [ 3 , 4 , 5 , 6 , 7 , 8 ]. These compounds exhibit excellent properties at relatively low densities, have extremely high melting points due to the strong bonds of intra- and interclusters B 12 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 For α-B, we get a ¼ 5:07 in the QHA at 298 K, while experiments show a ¼ 5:0623(3) Å. 55 The overestimation for fcc-Al and α-B is 0.49% and 0.15%, respectively. For stoichiometric AlB 2 , the overestimation is, on average, 0.50% for a and 1.64% for c. Meanwhile, for the isostructural diboride TiB 2 , a similar comparison between experiments and theory on the quasiharmonic level using GGA yields an overestimation of only 0.40% and 0.39% for the a and c lattice parameters, respectively.…”
Section: Thermal Expansionmentioning
confidence: 85%
“…However, mechanical properties of the composites, such as the hardness, show no pronounced improvement even as the mass ratio of boron carbide or other additives is substantially increased under conventional sintering scenarios, which might be owing to the entrapped porosity present in additives (24,25). Other factors such as the inconsistency of the thermal expansion coefficients of the matrix and additive components can further exacerbate the interface mismatches between the diboride and additive phases (26)(27)(28), compromising the mechanical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%